(untitled) (Journal of Pure and Applied Sciences (Science Forum), 2025)
This study presents the petrographic and chemical analyses of the coal within the Upper Benue Trough to determine the paleodepositional setting of the coal deposits. The Upper Benue Trough (UBT) is a basin that extends in a NEE-SSW direction from the Gulf of Guinea to the South of Chad basin. The UBT is divided into two namely Yola Arm and the Gongola Arm where the coal was hosted in the Gombe and Lamza Formation. A total of seven (7) samples were examined from 4 coal localities in the studied area.Chemical analyses were conducted at the University of Witwatersrand, Coal Laboratory in the School of Chemical and Metallurgy Engineering (SCHME) The equipment used is the Perkin Elmer thermogravimetric analyzer (TGA) while the Dry-Cal bomb calorimeter is for gross calorific value (GCV). The procedure for operating the bomb calorimeter is adopted after SANS 1928:2009/ ISO 1928:2009, and the ultimate analysis was adoptedafterSANS17247:2006/ISO 17247:2005. The petrographic blocks were subjected to grinding and polishing using SANS /ISO7404-2 (2009). Vitrinite reflectance measurement was carried out largely based on SANS /ISO 7404 part 5 (1994). The proximate analysis revealed the moisture content (MCareal aver.6.8Wt.%), volatile matter (VM areal aver.27.7wt.%), fixed carbon (FC areal aver.48.4wt.%) with the ash yield (areal aver.17.6 wt.%) calculated by difference. The gross calorific value areal average. 23.01 MJ/Kg with a low sulphur content (areal aver. 0.85% daf). The average data for C and H values are 74.30 wt.%, and 5.88 wt.% respectively, while that of N, S, and O are 1.72 wt.%, 0.85 wt.%, and 16.46wt.% respectively. The distribution of the maceral groups with vitrinite as the dominant maceral, followed by varied inertinite, mineral matter and liptinite. The mean random reflectance measurement value of the coals (0.53 % RoV) points to low-rank-lignite-bituminous rank coal. The chemical analyses display a y low ash, low sulphur and high moisture content in the coal samples within the three sub-regions of the Benue Trough typical of the Cretaceous coals. Given the modified equations and the plots used, understanding the depositional environment accurately from just a single model is quite challenging